Expression of tetanus toxin Fragment C in tobacco chloroplasts - Tregoning, John S. (Oxford University Press, 2003)
Fragment C (TetC) is a non-toxic 47 kDa polypeptide fragment of tetanus toxin that can be used as a subunit vaccine against tetanus. Expression of TetC in Escherichia coli and yeast was dependent on the availability of synthetic genes that were required to improve translation efficiency and stabilize the mRNA. To explore the feasibility of producing TetC in tobacco leaves, we attempted expression of both the bacterial high-AT (72.3% AT) and the synthetic higher-GC genes (52.5% AT) in tobacco chloroplasts. We report here that the bacterial high-AT mRNA is stable in tobacco chloroplasts. Significant TetC accumulation was obtained from both genes, 25 and 10% of total soluble cellular protein, respectively, proving the versatility of plastids for expression of unmodified high-AT and high-GC genes. Mucosal immunization of mice with the plastid- produced TetC induced protective levels of TetC antibodies. Thus, expression of TetC in chloroplasts provides a potential route towards the development of a safe, plant-based tetanus vaccine for nasal and oral applications.